Evaluating auditory stream segregation of SAM tone sequences by subjective and objective psychoacoustical tasks, and brain activity - Dolležal, Lena-Vanessa; Brechmann, André; Klump, Georg M.; Deike, Susann (Frontiers in Neuroscience, 2014)
Auditory stream segregation refers to a segregated percept of signal streams with different acoustic features. Different approaches have been pursued in studies of stream segregation. In psychoacoustics, stream segregation has mostly been investigated with a subjective task asking the subjects to report their percept. Few studies have applied an objective task in which stream segregation is evaluated indirectly by determining thresholds for a percept that depends on whether auditory streams are segregated or not. Furthermore, both perceptual measures and physiological measures of brain activity have been employed but only little is known about their relation. How the results from different tasks and measures are related is evaluated in the present study using examples relying on the ABA- stimulation paradigm that apply the same stimuli. We presented A and B signals that were sinusoidally amplitude modulated (SAM) tones providing purely temporal, spectral or both types of cues to evaluate perceptual stream segregation and its physiological correlate. Which types of cues are most prominent was determined by the choice of carrier and modulation frequencies (fmod) of the signals. In the subjective task subjects reported their percept and in the objective task we measured their sensitivity for detecting time-shifts of B signals in an ABA- sequence. As a further measure of processes underlying stream segregation we employed functional magnetic resonance imaging (fMRI). SAM tone parameters were chosen to evoke an integrated (1-stream), a segregated (2-stream) or an ambiguous percept by adjusting the fmod difference between A and B tones (∆fmod). The results of both psychoacoustical tasks are significantly correlated. BOLD responses in fMRI depend on ∆fmod between A and B SAM tones. The effect of ∆fmod, however, differs between auditory cortex and frontal regions suggesting differences in representation related to the degree of perceptual ambiguity of the sequences.